PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERORIENTASI MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS XI SMA - Resi Okta Safitri; Arnentis Arnentis; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to produce LKPD oriented guided inquiry learning model on the material structure and function of plant tissue to improve the thinking ability krtitis learners class XI SMA. This research was conducted at the Laboratory of Biology Education Department of PMIPA Faculty of Teacher Training and Education University of Riau and SMAN 1 Benai in June-October 2017. This type of research is development research by using ADDIE model. Research subject KD 3.3 Analyzing the relationship between cell structure in plant tissue and organ function in plants. The instruments of data collection are the LKPD assessment / validation sheets, and the students' response questionnaire. The assessment / validation sheet consists of 3 aspects: design aspect, pedagogic aspect and content aspect. The data obtained from the development of LKPD oriented guided inquiry learning model on the material structure and function of plant tissue to improve critical thinking ability of class XI high school students who have validated 4 (four) validators, consisting of 2 lecturers and 2 high school teachers. Furthermore, I tested and also distributed a questionnaire addressed to Biology Education students semester 5 as many as 15 people. After trial I, LKPD was revised. Then conducted II trials as well as distributing a questionnaire aimed at 20 students of grade XI SMAN 1 Benai. The end result of trial I and II is the questionnaire of the respondents' response. The validation result shows the mean score of design aspect of 3 LKPD developed is 3.49 categories is very valid, the pedagogic aspect score is 3.30 valid category, and the mean content aspect score is 3.55 valid categories. The average score of all aspects of the three LKPD is 3.45 valid categories. The results of the first test showed an average score of 3.29 with very good category. The results of the second trial showed the average score of 3.42 with good category. Results of analysis of the students' answers on LKPD oriented Guided Inquiry learning model to improve the ability of critical thinking is 92.2 with very good category.Keywords: Student Worksheets, Guided Inquiry, Critical Thinking